MELACAK PERAN KYAI-SANTRI DALAM POLITIK KEBANGSAAN DI INDONESIA - Fifi Nofiaturrahmah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
Political movement of Kyai in combating colonialism, defending the independence, and Ful Filling and maintening is significant. As noted in the history Kyai plays in many levels and historical moment. At least there are 5 phase for the political movement of Kyai, Movement in the revolution era, movement in the Rising and new order era and reformation era. This article aims to analyze the typology of Kyai’s movement in every phase of time done by Kyai. The result show us that in every historical phase Kyai has implemented nation state politic as spirit of his struggle. And in reformation era, Kyai movement focused on practiced politic and much more bring madharat than goodness. So that it’s bring the image of Kyai be negative in front of his community. So that to giving back the function of Kyai as social power in society Kyai should play in the nation state politic, not the politic of interest.